Incorporating gendered analysis and flexibility in heavy work investment studies: a systematic literature review - Escudero-Guirado, Carmen; Fernández-Rodríguez, Lourdes; Nájera-Sánchez, Juan-José (Frontiers in Psychology, 2024)
Significant impacts of heavy work investment on employee well-being and organizational performance have prompted its increasing importance as a research topic. The findings about good or evil of these repercussions are nonetheless inconclusive. The intersection of Heavy Work Investment construct with gender has not been explicitly addressed by previous literature review and research. Besides, the relevance of flexibility for women, as one of the key factors for successful work-family balance management, still remains to be analyzed. A literature review on Heavy Work Investment was conducted using the SPAR-4-SLR protocol, wherein 83 articles were selected from a pool of 208 previously identified works. Bibliometric and content analysis techniques were employed, including co-word analysis, to evaluate research production, impact, and trends in the gender perspective within Heavy Work Investment. As a result, a strategic diagram illustrates thematic topics, providing a clear understanding of the field's structure and evolution. Six thematic groups were identified, around work-family conflict as the central theme. The explicit consideration of a gender perspective in literature involves nuanced differences regarding the conclusions of studies with a broader focus. First, the emerging prominence of studies on China and Japan becomes clear with gender as the specific focus of the review, aiming to clarify the experiences women face in more traditional societies with a more decisive division of roles. Second, there is a shift in interest regarding the analysis of Job Demands and Job Resources. Despite the apparent decline in interest in the former, the focus in gender literature clearly shifts towards the side of Job Resources, showing potential for the future. It could be understood that in a context of talent war and employee retention efforts, priority is given to better understanding of facilitating individual and organizational factors for work-life balance, especially for women. Future research areas are identified, including gender differences in organizational support and the impact of flexible work on the work-life balance, providing valuable insights for academia, practitioners, and organizations. The need for more comprehensive cross-cultural and gender research is also made clear.